Formação continuada em serviço e o Programa Gestar: um estudo sobre a prática de professores de língua portuguesa - Nascimento, Tânia Maria Nunes (2015)
This research aims to investigate the teaching practice undertaken by teachers with training in Portuguese, turning their attention to the development of activities in the classroom, with more specific interest in knowing how these teachers with training in Learning Management Program - Gestar make use of their knowledge to perform the Didactic Transposition. The research develops from three questions: a) Do the teachers who participate in Gestar formation program have their practice founded on the epistemological guiding principles of the course? b) What is the conception of language that permeates the Portuguese language these teachers' teaching activities? c) How do the teachers with training in Gestar Program appropriate the knowledge and performs the Didactic Transposition? The research fits the principles of qualitative research and based on that foundation the individual interviews content and data collected during the observations of the Portuguese classes from four teachers were analyzed. The research aligns with the theoretical contributions of Applied Linguistics and uses the concept from Bakhtin’s Theory on Language (2012), specifically the interactions between subject and language as a social, historical and dynamic phenomenon, and refers also to the Didactic Transposition Theory following Chevallard’s assumption (1991) and Rafael’s discussions (2001), and other relevant theorists to the discussion. As a result of our analysis we found that the Gestar formation imprints a low range in changing on the Portuguese teaching classroom practices, although it exert high influence in teacher’s education and understanding of the language and education concepts that should guide professional practice. The results lead us to reflect the need for strengthening and deepening the discussions about the transposition of academic knowledge into school knowledge.